Mapping of Potential Damages Area in Lombok Island Base on Microtremor Data - Ridwan, M.; Yatini, Y.; Pramono, S. (Jurnal Pendidikan Fisika Indonesia, 2021)
Lombok Island and its surrounding is an area that has a high seismicitys level because it is located in the Eastern Sunda Arc. Tectonically, Lombok Island located between the Indo-Australia plate collision zone with Eurasia in the south and the fult of the backarc Bali-Flores in the north. This research’s purposed to determine the distribution of vulnerability index and peak ground acceleration value are used to determine the GSS value, so mapping of potential damage areas could be done. The microtremor data taken on 32 observation points distributed in Lombok Island. Microtremor data is analysed using Horizontal to Vertical Spectral Ratio (HVSR) method to get seismic vulnerability index (Kg) and dominant period. Determination of Peak Ground Acceleration (PGA) value using data from the MASE Stasion measurement results based on earthquake events on August 5, 2018. Seismic vulnerability index and peak ground acceleration value are used to determine the GSS value. Determination of potential damage area using analysis of the dominant period, seismic vulnerability indexs and Ground Shear Strain values. The results of this research showed that seismic vulneribility index value in research area is about 0,029 sekon to 1,360 sekon, seismic vulneribility index value is about 0,56 to 189,92 and GSS value is about 2,52 x 10-5 to 8,46 x 10-3. The results show that the light damage dominated in East Lombok Districts, the moderate damage is on Mataram City and it dominated in West Lombok Districts. The heavy damage present in the most parts of West Lombok Districts.